Composite binder, preparation method and lithium ion battery

By using an improved composite adhesive in lithium-ion batteries, the problem of insufficient adhesive in carbon black dispersion is solved, and a more uniform conductive network and higher electrode performance is achieved.

CN119463792APending Publication Date: 2025-02-18SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411473480.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The binder in existing lithium-ion batteries does not perform well in carbon black dispersion, resulting in uneven conductivity of the electrode composite material and affecting the electrode performance.

Method used

Provided is a composite binder, including polymer I, whose structure is copolymerized by vinylidene fluoride with an amino group-containing monomer and combined with a polyethylene glycol polymer through Michael addition reaction to form an improved carbon black dispersion binder.

Benefits of technology

By improving the dispersion of carbon black, the conductive network of the electrode composite material is more uniform, the conductive performance and structural stability of the electrode are improved, and the service life of the electrode is extended.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a composite binder, a preparation method and a lithium ion battery. The composite binder comprises a polymer I as shown in a formula I. Amino groups, imino groups and polar fluorine atoms in the polymer I can enhance the bonding force of the polymer, and meanwhile, polar oxygen atoms in polyethylene glycol groups can be combined with hydroxyl groups in carbon black, so that when the composite binder is mixed with the carbon black, the dispersity of the carbon black can be improved, a conductive network of an electrode composite material is more uniform, and the conductivity of the electrode composite material is improved. And the conductivity of the electrode is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of battery materials, and specifically relates to a composite binder and a preparation method thereof, and a lithium-ion battery. Background Art

[0002] The performance of the electrode sheet of a lithium-ion battery is one of the key factors that determine the performance of the lithium-ion battery. It is mainly composed of electrode active materials, conductive agents, binders and current collectors. The binder is used to bond the electrode active materials and conductive agent particles, and at the same time bond them to the surface of the current collector. Therefore, the performance of the binder is closely related to the electrochemical performance of the ion battery.

[0003] At present, the most commonly used binders for lithium-ion batteries are polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC) and styrene-butadiene rubber (SBR). PVDF binder is a relatively mature binder in terms of process technology and has good bonding properties. However, traditional PVDF binders are insufficient in carbon black dispersion, which easily leads to uneven conductive networks of electrode composite materials and affects the performance of the electrode. Summary of the invention

[0004] The present application provides a composite binder and a preparation method thereof, and a lithium ion battery, aiming to solve the problem that the binder in the existing lithium ion battery has unsatisfactory performance in carbon black dispersion.

[0005] The first embodiment of the present application provides a composite adhesive, including a polymer I as shown in Formula I:

[0006]

[0007] Wherein, R1, R2 and R3 are each independently selected from any one of H, substituted or unsubstituted C1-C6 hydrocarbon group, imino group, carbonyl group, ester group and ether bond, and the substituent replacing the C1-C6 hydrocarbon group includes at least one of alkyl group, amino group, hydroxyl group and carboxyl group;

[0008] R4 is selected from at least one of amino, pyrimidinyl and pyrazolyl;

[0009] R5 is selected from H and substituted or unsubstituted C1-C 16 Hydrocarbon, replacing the C1~C 16 The substituent of the hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group;

[0010] n=5~10, m=300~400.

[0011] In some embodiments, R1, R2 and R3 are each independently selected from any one of a C1-C6 hydrocarbon group and an imino group;

[0012] R4 is an amino group;

[0013] R5 is selected from C1~C 16 alkyl.

[0014] In some embodiments, in the polymer I, n / m=0.015-0.03.

[0015] In some embodiments, the molecular weight of polymer I is 5×10 5 ~9×10 5 .

[0016] The second embodiment of the present application provides a method for preparing a composite adhesive, which is used to prepare the composite adhesive in any of the above embodiments, comprising the following steps:

[0017] Providing a first monomer and a second monomer to carry out a condensation reaction;

[0018] Adding polymer II to carry out Michael addition reaction;

[0019] Add a capping agent and react to obtain a polymer I, the structural formula of which is shown in Formula I:

[0020]

[0021] Wherein, R1, R2 and R3 are each independently selected from any one of a substituted or unsubstituted C1-C6 hydrocarbon group, an imino group, a carbonyl group, an ester group and an ether bond, and the substituent replacing the C1-C6 hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group;

[0022] R4 is selected from at least one of amino, pyrimidinyl and pyrazolyl;

[0023] R5 is selected from H and substituted or unsubstituted C1-C 16 Hydrocarbon, replacing the C1~C 16 The substituent of the hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group;

[0024] n=5~10, m=300~400.

[0025] In some embodiments, the first monomer is vinylidene fluoride;

[0026] The second monomer includes any one of diethylenetriamine, triethylenetetramine, 1-(3-aminopropyl)imidazole, and 4-(2-aminoethyl)pyridine;

[0027] The polymer II is polyethylene glycol diacrylate, wherein the molecular weight of the polymer II is 600-1500.

[0028] In some embodiments, the end-capping agent includes any one of 1,3,9-triaminododecane, 1,7-diamino-3,6,9-trioxytridecane, 1,7-diaminotridecane, and 1,3,9-triamino-2,4,6-trioxydodecane.

[0029] In some embodiments, the molar ratio of the first monomer, the second monomer, the polymer II and the end-capping agent is 100-200: 100-200: 100-200: 1-2.

[0030] In some embodiments, the condensation reaction temperature is 50° C. and the reaction time is 3 h.

[0031] In some embodiments, the temperature of the Michael addition reaction is 120° C. and the time is 3 h.

[0032] A third embodiment of the present application provides a lithium-ion battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises the composite binder in any of the above embodiments.

[0033] The present application provides a composite binder, comprising a polymer I as shown in formula I, wherein R1, R2 and R3 are each independently selected from any one of H, a substituted or unsubstituted C1-C6 hydrocarbon group, an imino group, a carbonyl group, an ester group and an ether bond, and the substituent replacing the C1-C6 hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group; R4 and R5 are each independently selected from any one of a substituted or unsubstituted C1-C 16 Hydrocarbon, substituted C1~C 16 The substituent of the hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group; n=5-10, m=300-400. The amine group, the imino group and the polar fluorine atom in the polymer I can enhance the bonding force of the polymer, and at the same time, the polar oxygen atom in the polyethylene glycol group can combine with the hydroxyl group in the carbon black, so that the composite binder can improve the dispersion of the carbon black when mixed with the carbon black, thereby making the conductive network of the electrode composite material more uniform and improving the conductive performance of the electrode. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0035] In the description of the present application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or can communicate with each other; it can be directly connected, or indirectly connected through an intermediate medium, or indirectly connected through a pipe or pipeline, and it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In the description of the present application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. In addition, the terms "first" and "second" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more features.

[0036] The first embodiment of the present application provides a composite adhesive, including a polymer I as shown in Formula I:

[0037]

[0038] Wherein, R1, R2 and R3 are each independently selected from any one of substituted or unsubstituted C1-C6 hydrocarbon groups, imino groups, carbonyl groups, ester groups and ether bonds, and the substituents for the C1-C6 hydrocarbon groups include at least one of alkyl groups, amino groups, hydroxyl groups and carboxyl groups;

[0039] R4 is selected from at least one of amino, pyrimidinyl and pyrazolyl;

[0040] R5 is selected from H and substituted or unsubstituted C1-C 16 Hydrocarbon, substituted C1~C 16 The substituent of the hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group;

[0041] n=5~10, m=300~400.

[0042] The repeating unit in polymer I is obtained by copolymerizing a monomer containing an amino group with vinylidene fluoride, and then reacting with a polyethylene glycol polymer to undergo a Michael addition reaction. The polar fluorine atoms in vinylidene fluoride have a high electronegativity. When the binder containing polymer I comes into contact with an object, it can form a chemical bond with the electrophilic groups (such as hydroxyl groups, carboxyl groups, etc.) on the surface of the object, thereby improving the bonding performance of the binder. By modifying vinylidene fluoride with a monomer containing an amino group, the amino polar sites and imino polar sites can be further increased in the polymer, and it can continue to form a chemical bond with the electrophilic groups on the surface of the object, thereby further improving the bonding force of the binder. On the other hand, the polar oxygen atoms in the polyethylene glycol group can combine with the hydroxyl groups in carbon black, so that the composite binder can improve the dispersibility of carbon black when mixed with carbon black, thereby making the conductive network of the electrode composite material more uniform, improving the conductive performance of the electrode, enhancing the structural stability of the electrode material, and extending the service life of the electrode.

[0043] In some embodiments, R1, R2 and R3 are each independently selected from any one of a C1-C6 hydrocarbon group and an imino group;

[0044] R4 is an amino group;

[0045] R5 is selected from C1~C 16 alkyl.

[0046] When R4 is an amino group and R5 is a C1-C 16 When the polymer I is alkyl, there are more amino polar sites, which makes it easier to form chemical bonds with electrophilic groups on the surface of the object, thereby further improving the bonding force of the adhesive.

[0047] In some embodiments, in polymer I, n / m=0.015-0.3.

[0048] It is understood that the value of n / m can be any value among 0.015, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3 or a range between any two values. When the ratio of n / m satisfies the above value relationship, the polymer I can contain sufficient polar oxygen atoms, so that the binder can have a better performance in dispersing carbon black.

[0049] In some embodiments, the molecular weight of polymer I is 5×10 5 ~9×10 5 .

[0050] The molecular weight in this application refers to the weight average molecular weight of the polymer. It is understood that the molecular weight of polymer I can be 5×10 5 , 6×10 5 ,7×105 , 8×10 5 ,9×10 5 The polymer with higher molecular weight has higher viscosity and bonding strength, but its fluidity is relatively low, while the polymer with lower molecular weight has better fluidity, but its viscosity and bonding strength are relatively low. When the molecular weight of polymer I meets the above value range, it can ensure that the adhesive has both ideal bonding strength and fluidity.

[0051] The second embodiment of the present application provides a method for preparing a composite adhesive, which is used to prepare the composite adhesive in any of the above embodiments, comprising the following steps:

[0052] Providing a first monomer and a second monomer to carry out a condensation reaction;

[0053] Adding polymer II to carry out Michael addition reaction;

[0054] Add a capping agent and react to obtain polymer I. The structural formula of polymer I is shown in formula I:

[0055]

[0056] Wherein, R1, R2 and R3 are each independently selected from any one of substituted or unsubstituted C1-C6 hydrocarbon groups, imino groups, carbonyl groups, ester groups and ether bonds, and the substituents for the C1-C6 hydrocarbon groups include at least one of alkyl groups, amino groups, hydroxyl groups and carboxyl groups;

[0057] R4 is selected from at least one of amino, pyrimidinyl and pyrazolyl;

[0058] R5 is selected from H and substituted or unsubstituted C1-C 16 Hydrocarbon, substituted C1~C 16 The substituent of the hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group;

[0059] n=5~10, m=300~400.

[0060] The composite binder provided in the embodiment of the present application is prepared by condensing two monomers and then performing a Michael addition reaction with polymer II, which can form a linear high molecular polymer and retain polar functional groups. At the same time, the process flow is simple and easy to operate.

[0061] In some embodiments, the first monomer is vinylidene fluoride;

[0062] The second monomer includes any one of diethylenetriamine, triethylenetetramine, 1-(3-aminopropyl)imidazole, and 4-(2-aminoethyl)pyridine;

[0063] The polymer II is polyethylene glycol diacrylate, wherein the molecular weight of the polymer II is 600-1500.

[0064] It is understood that the molecular weight of polymer II can be any value among 600, 800, 1000, 1200, 1400, 1500 or a range between any two values. When the molecular weight of polymer II meets the above range, it can ensure that polymer II contains sufficient polar oxygen atoms.

[0065] In some embodiments, the capping agent includes any one of 1,3,9-triaminododecane, 1,7-diamino-3,6,9-trioxytridecane, 1,7-diaminotridecane, and 1,3,9-triamino-2,4,6-trioxydodecane.

[0066] In some embodiments, the molar ratio of the first monomer, the second monomer, the polymer II, and the end-capping agent is 100-200: 100-200: 100-200: 1-2.

[0067] When the molar ratio of the first monomer, the second monomer, the polymer II and the end-capping agent meets the above value range, a structural unit that meets the requirements can be generated.

[0068] In some embodiments, the condensation reaction temperature is 50° C. and the reaction time is 3 h.

[0069] When the temperature and time of the condensation reaction meet the above value range, the first monomer and the second monomer can react to obtain the dehydrogenation product PVDF-g-DETA.

[0070] In some embodiments, the temperature of the Michael addition reaction is 120° C. and the time is 3 h.

[0071] When the temperature and time of the Michael addition reaction meet the above range, it can ensure that the first monomer, the second monomer and the polymer II react to form the polymer I while avoiding excessive polymerization and self-polymerization, and further make the molecular weight of the generated polymer meet 5×10 5 ~9×10 5 range to ensure that the adhesive has both ideal bonding strength and fluidity.

[0072] A third embodiment of the present application provides a lithium-ion battery, including a positive electrode sheet, wherein the positive electrode sheet includes the composite binder in any of the above embodiments.

[0073] The following is a description of the composite binder, preparation method, and lithium-ion battery provided by the present application in conjunction with specific embodiments:

[0074] Example 1

[0075] Embodiment 1 provides a composite adhesive, which is prepared by the following steps:

[0076] 1) Dissolve 1mmol VDF in N-methylpyrrolidone (NMP) solvent, add 1mmol DETA, then add 0.1g NaOH, stir at 100℃ for 4h, introduce nitrogen for 30min, then add 0.1g dibenzoyl peroxide, and react at 150℃ for 10h. After the reaction is completed, let it stand overnight, add 500ml deionized water, pour out the supernatant, wash the lower layer of condensate with deionized water by centrifugation, and then dialyze to remove the alkali until the pH is close to 7, to obtain the intermediate product PVDF-g-DETA.

[0077] 2) 0.1 g of PVDF-g-DETA was dissolved in 3 ml of DMSO, 0.1 g of polyethylene glycol diacrylate was added, and the mixture was stirred at 120° C. for 3 h, then cooled, capped with 1,3,9-triaminododecane as a capping agent, and heated to 50° C. for reaction for 3 h to obtain polymer I.

[0078] Embodiment 1 also provides a lithium ion battery, comprising the composite binder prepared by the above method, which is prepared by the following steps:

[0079] 1) Preparation of positive electrode sheet of battery:

[0080] Add 2g of the above composite binder to 60g of NMP, stir until completely dissolved, add 2g of conductive carbon black (purchased from Jiaozuo Hexing Chemical Industry Co., Ltd.), mix evenly, add 96g of LiFePO4 (purchased from Changzhou Liyuan New Energy Technology Co., Ltd.) powder to the above mixed solution under slow stirring, stir at high speed for 2 hours to obtain positive electrode slurry. Coat on aluminum foil with a thickness of 15 microns, dry at 110-120°C, and roll to obtain positive electrode sheet.

[0081] 2) Preparation of battery negative electrode sheet:

[0082] Natural graphite (purchased from BTR New Materials Co., Ltd.), carbon black SP (purchased from Jiaozuo Hexing Chemical Industry Co., Ltd.), binder SBR (purchased from BASF SE, Germany) and sodium carboxymethyl cellulose (CMC) (purchased from Changshu Weiyi Technology Co., Ltd.) were mixed evenly in deionized water according to the weight ratio of graphite: SP: SBR: CMC mass ratio of 96.2: 1.5: 2.3: 1. Coated on both sides of copper foil with a thickness of 10 microns, dried at 60-75°C, and rolled to obtain the negative electrode sheet.

[0083] 3) Preparation of lithium-ion batteries:

[0084] Preparation of electrolyte: The concentration of LiPF6 is 1 mol / L, and the mass ratio of the mixed solvent components is ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 3:5:2. The prepared negative electrode sheet, positive electrode sheet, polypropylene separator (purchased from Celgard Co., Ltd., USA) and electrolyte are assembled to obtain a lithium-ion battery.

[0085] Embodiments 2 to 6

[0086] The preparation methods of the composite binders and lithium-ion batteries provided in Examples 2 to 6 are consistent with those in Example 1, with only the selection of raw materials and process parameters being adjusted.

[0087] Comparative Example 1

[0088] Comparative Example 1: A lithium ion battery is prepared using polyvinylidene fluoride as a binder, and the preparation is specifically carried out through the following steps:

[0089] 1) Preparation of positive electrode sheet of battery:

[0090] Add 2g of polyvinylidene fluoride to 60g of NMP, stir until completely dissolved, add 2g of conductive carbon black (purchased from Jiaozuo Hexing Chemical Industry Co., Ltd.), mix evenly, add 96g of LiFePO4 (purchased from Changzhou Liyuan New Energy Technology Co., Ltd.) powder to the above mixed solution under slow stirring, stir at high speed for 2 hours to prepare positive electrode slurry. Coat on aluminum foil with a thickness of 15 microns, dry at 110-120°C, and roll to obtain positive electrode sheet.

[0091] 2) Preparation of battery negative electrode sheet:

[0092] Natural graphite (purchased from BTR New Materials Co., Ltd.), carbon black SP (purchased from Jiaozuo Hexing Chemical Industry Co., Ltd.), binder SBR (purchased from BASF SE, Germany) and sodium carboxymethyl cellulose (CMC) (purchased from Changshu Weiyi Technology Co., Ltd.) were mixed evenly in deionized water according to the weight ratio of graphite: SP: SBR: CMC mass ratio of 96.2: 1.5: 2.3: 1. Coated on both sides of copper foil with a thickness of 10 microns, dried at 60-75°C, and rolled to obtain the negative electrode sheet.

[0093] 3) Preparation of lithium-ion batteries:

[0094] Preparation of electrolyte: The concentration of LiPF6 is 1 mol / L, and the mass ratio of the mixed solvent components is ethylene carbonate (EC): ethyl methyl carbonate (EMC): diethyl carbonate (DEC) = 3:5:2. The prepared negative electrode sheet, positive electrode sheet, polypropylene separator (purchased from Celgard Co., Ltd., USA) and electrolyte are assembled to obtain a lithium-ion battery.

[0095] Comparative Examples 2-3

[0096] The preparation methods of the composite binder and lithium-ion battery provided in Comparative Examples 2 to 3 are consistent with those in Example 1, with only the selection of raw materials and process parameters being adjusted.

[0097] The reactants and related process conditions in Examples 1 to 6 and Comparative Examples 1 to 3 are shown in Table 1.

[0098] Table 1

[0099]

[0100] The electrochemical performance test of the lithium ion batteries in the above embodiments and comparative examples is carried out as follows:

[0101] 1) Contact impedance: The rolled positive electrode sheet was cut into 2cm*2cm film sheets, and the overall resistivity of the positive electrode film was directly measured by Suzhou lattice four-probe tester;

[0102] 2) Discharge rate performance:

[0103] The lithium-ion battery was charged to 3.8V at a current of 0.1C, and after 10 minutes, it was discharged to 2.0V at a current of 0.5C; the same method was used to change the discharge current to 1C, 5C, 10C, and 15C, and the discharge capacity was recorded each time. The data is shown in Table 4.

[0104] 3) Cycle performance: The battery was placed in a constant temperature box at 25°C and 45°C, and the capacity retention rate of the battery after 200 cycles at different temperature conditions was calculated by charging and discharging at 1C / 1C.

[0105] 4) Constant voltage intermittent titration (PITT) test: Let the assembled battery stand for 12 hours, and then perform three cycles of charge and discharge activation at a rate of 0.1C. Then start constant voltage charging from a voltage of 3.6V until the current is less than 2A (in this test, the constant voltage charging is to a current of 0.2A), and continue constant voltage charging for 30 minutes to stabilize the voltage. Each voltage step is set to 0.025V until the charge cut-off voltage of 4.3V is reached. The PITT test applies a potential pulse with a fixed step of 0.02V to the electrode system in equilibrium, and then records the change of the battery current over time at different potentials. The lithium ion diffusion coefficient at different potentials is calculated based on the current change data at different voltages. The calculation formula is:

[0106] ξ=-[4L 2 / π 2 ]dln(I) / d

[0107] Wherein, is the diffusion coefficient of lithium ions in the solid phase, I(t) is the transient current (mA) at time t(s), and L is the electrode thickness or the particle size of the material (cm).

[0108] The test results are shown in Table 2.

[0109] Table 2

[0110]

[0111] According to Table 2, it can be seen that the resistivity of the battery prepared by the composite binder obtained by the scheme provided by the present application has been significantly reduced, and the battery capacity and cycle performance have been significantly improved. The composite binder containing polymer I formed by the condensation reaction and Michael addition reaction of different monomers provided by the present application has good performance in terms of battery performance. According to Comparative Example 1, it can be seen that the resistivity of the battery prepared by using polyvinylidene fluoride as a binder is high, and the battery capacity and cycle performance are not as good as the batteries in Examples 1 to 6; according to Comparative Examples 2 to 3, it can be seen that when the ratio of vinylidene fluoride to polyethylene glycol diacrylate is too high or too low, it will affect the performance of polymer I in terms of bonding performance, and then affect the electrical performance and cycle performance of the battery, but the overall performance is still better than the battery using polyvinylidene fluoride as a binder in Comparative Example 1.

[0112] The above is a detailed introduction to a composite adhesive and a preparation method, and a lithium-ion battery provided in the embodiments of the present application. Specific examples are used in the present application to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solution and its core idea of ​​the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A composite adhesive, characterized in that: Including a polymer I as shown in formula I: Wherein, R1, R2 and R3 are each independently selected from any one of a substituted or unsubstituted C1-C6 hydrocarbon group, an imino group, a carbonyl group, an ester group and an ether bond, and the substituent replacing the C1-C6 hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group; R4 is selected from at least one of amino, pyrimidinyl and pyrazolyl; R5 is selected from H and substituted or unsubstituted C1-C 16 Any one of the hydrocarbon groups replaces the C1 to C 16 The substituent of the hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group; n=5~10, m=300~400.

2. A composite adhesive according to claim 1, characterized in that: R1, R2 and R3 are each independently selected from any one of a C1-C6 hydrocarbon group and an imino group; R4 is an amino group; R5 is selected from C1~C 16 alkyl.

3. A composite adhesive according to claim 1, characterized in that: In the polymer I, n / m=0.015 to 0.

03.

4. A composite adhesive according to claim 1, characterized in that: The molecular weight of the polymer I is 5×10 5 ~9×10 5 .

5. A method for preparing a composite adhesive as claimed in any one of claims 1 to 4, characterized in that: The steps include: Providing a first monomer and a second monomer to carry out a condensation reaction; Adding polymer II to carry out Michael addition reaction; Add a capping agent and react to obtain a polymer I, the structural formula of which is shown in Formula I: Wherein, R1, R2 and R3 are each independently selected from any one of a substituted or unsubstituted C1-C6 hydrocarbon group, an imino group, a carbonyl group, an ester group and an ether bond, and the substituent replacing the C1-C6 hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group; R4 is selected from at least one of amino, pyrimidinyl and pyrazolyl; R5 is selected from H and substituted or unsubstituted C1-C 16 Hydrocarbon, replacing the C1~C 16 The substituent of the hydrocarbon group includes at least one of an alkyl group, an amino group, a hydroxyl group and a carboxyl group; n=5~10, m=300~400.

6. The method for preparing a composite adhesive according to claim 5, characterized in that: The first monomer is vinylidene fluoride; The second monomer includes any one of diethylenetriamine, triethylenetetramine, 1-(3-aminopropyl)imidazole, and 4-(2-aminoethyl)pyridine; The polymer II includes polyethylene glycol diacrylate, wherein the molecular weight of the polymer II is 600-1500.

7. The method for preparing a composite adhesive according to claim 5, characterized in that: The end-capping agent includes any one of 1,3,9-triaminododecane, 1,7-diamino-3,6,9-trioxytridecane, 1,7-diaminotridecane, and 1,3,9-triamino-2,4,6-trioxydodecane.

8. The method for preparing a composite adhesive according to claim 5, characterized in that: The molar ratio of the first monomer, the second monomer, the polymer II and the end-capping agent is 100-200:100-200:100-200:1-2.

9. The method for preparing a composite adhesive according to claim 5, characterized in that: The condensation reaction temperature is 50° C. and the reaction time is 3 hours; and / or, The temperature of the Michael addition reaction is 120° C. and the time is 3 h.

10. A lithium ion battery, comprising a positive electrode sheet, characterized in that: The positive electrode sheet comprises the composite binder as described in any one of claims 1 to 4 or comprises the composite binder prepared by the preparation method as described in claims 5 to 9.